2019
DOI: 10.2147/jir.s203714
|View full text |Cite
|
Sign up to set email alerts
|

<p>ELR positive CXCL chemokines are highly expressed in an animal model of ulcerative colitis</p>

Abstract: Background: The presence of neutrophil-rich inflammation in colon tissues of patients with ulcerative colitis (UC) is one of the most important histological characteristics of this disease. However, the expression of CXCL chemokines governing the infiltration of neutrophils in UC has not been well elucidated. Materials and methods: In this experimental study, the UC model was induced in Wistar rats by administration of 2 mL 4% acetic acid into the large colon through the rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Both of them are the risk genes and were verified upregulated in UC. 47 Type 17 immunity involved in the inflammation in the pathogenesis of ulcerative colitis has been implicated, 48,49 and type 17 immunity were derived by anticommensal response or antigen presentation in UC. 50,51 We found in the DEGs in epithelial and stromal lineages that Th17 signals were increased not only in the inflamed tissue, but also in the uninflamed control tissue, with the bacteriostatic molecule LCN2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Both of them are the risk genes and were verified upregulated in UC. 47 Type 17 immunity involved in the inflammation in the pathogenesis of ulcerative colitis has been implicated, 48,49 and type 17 immunity were derived by anticommensal response or antigen presentation in UC. 50,51 We found in the DEGs in epithelial and stromal lineages that Th17 signals were increased not only in the inflamed tissue, but also in the uninflamed control tissue, with the bacteriostatic molecule LCN2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CXCL3 and CXCL8 are also closely related to UC and CRA. For example, it has been found that CXCL3 [28] and CXCL8 [40] participate in the pathogenesis of UC and can be used as therapeutic targets for UC. For CRA, a study by Mclean et al showed that the inflammatory cytokine genes CXCL1, CXCL2, CXCL3, CCL20, IL8 (CXCL8), CCL23, CCL19, CCL21, and CCL5are BioMed Research International 4) and CEACAM7 (carcinoembryonic antigen-related cell adhesion molecule 7) have been found to be associated with an unfavourable prognosis in CRC [41].…”
Section: Discussionmentioning
confidence: 99%
“…Some gene biomarkers, such as mRNA and miRNAs, have been previously identified to correlate with CRC and developed as diagnostic tools to predict the occurrence, progression, and prognosis of CRC [21][22][23][24]. However, the identification of biomarker genes has only been focused on a single stage of CRC in many studies [25][26][27][28]. By considering all stages of disease progression, researchers can identify more accurate and targeted diagnostic gene biomarkers to be applied in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…As it is reported, 17 ligands that bind to the CXC family of chemokines are identified; these ligands are known as CXCL1 to CXCL17. 22 The close relationship between these CXCLs is shown in Figures 3 and 4. The introduced CXCLs are linked mostly to the legionellosis, the collection of infections that are caused by Legionella penumophila.…”
Section: Discussionmentioning
confidence: 66%